2019
DOI: 10.1371/journal.pone.0215253
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting impacts of two weed species on lowbush blueberry fertilizer nitrogen uptake in a commercial field

Abstract: Numerous studies have speculated that lowbush blueberry ( Vaccinium angustifolium ) is less efficient than weed species at taking up inorganic nitrogen (N) derived from fertilizers, thus raising questions as to the effectiveness of N fertilization in commercial fields. However, competition for acquiring N as well as specific interactions between blueberry and companion weeds characterized by contrasted functional traits remain poorly documented. Here, we assessed fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…A previous 15 N-labelling study has shown that D . spicata specifically relies heavily on inorganic N fertilizer for producing its aboveground biomass [7]. The absence of an effect for the organic N fertilizer on the three plant species may have resulted from the specific organic fertilizer used.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous 15 N-labelling study has shown that D . spicata specifically relies heavily on inorganic N fertilizer for producing its aboveground biomass [7]. The absence of an effect for the organic N fertilizer on the three plant species may have resulted from the specific organic fertilizer used.…”
Section: Discussionmentioning
confidence: 99%
“…This commercial field is located near Saint-Eugène d’Argentenay in the Saguenay–Lac-Saint-Jean region, Quebec, Canada (48°59′N, 72°18′W), which contains 82% of Quebec’s commercial lowbush blueberry surface area [2]. A study was previously conducted on this field to assess the ability of the three aforementioned species to acquire 15 N from an inorganic fertilizer [7]. Soils in the lowbush blueberry stands are podzols characterized by fine sands that originate from fluvioglacial deposits.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations